Effect of Feeding Calf Starter Diets Containing Shrimp Waste Meal on Nutrient Utilization in Murrah Buffalo Calves - Aruna, K V N; Srinivas, D Kumar; Rao, E Raghava; Rao, S Jagadeeswara (Indian Journal of Animal Nutrition, 2020)
A 120-day growth trial was conducted using 20 Murrah buffalo calves (Avg. BW 71.0 Â± 1.6 kg) by randomly allotting them to four groups of 5 animals each to study the effect of replacing the protein content of soybean meal with shrimp waste meal at 0, 10, 20 and 30 % levels on nutrient utilization. Chemical composition (% DMB) indicated that shrimp waste meal was rich source of crude protein. Amino acid composition revealed that shrimp waste meal used in the present study is a rich source of serine. Fatty acid composition indicated that shrimp waste meal is rich in saturated fatty acids and also possesses considerable quantities of mono- and poly-unsaturated fatty acids which accounts for 34.86 % of total fatty acids. The digestibility of DM, OM, CP, EE, CF, NFE, NDF, ADF, hemi-cellulose and cellulose increased (P<0.01) in Murrah buffalo calves irrespective of the level of inclusion of shrimp waste meal in the diet. However, higher (P<0.01) digestibilities were observed at 10 % replacement level (T2) as compared to the other groups. The DM, DCP and TDN intakes of buffalo calves of all the groups were higher than the recommendations of ICAR (1998) indicating the adequacy and palatability of calf starter diets. The % DCP and TDN content were significantly higher (P<0.01) in T2 as compared to other treatments. It is concluded that replacement of the protein content of soybean meal with shrimp waste meal at 10 % level in calf starter diets resulted in improved digestibility of gross nutrients in buffalo calves.Â